2015
DOI: 10.17703/ijact.2015.3.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Tensile Strength of Butt Joint between AA6063 Aluminum Alloy and AISI304 Stainless Steel by Friction Stir Welding

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The authors of this study attributed the reduction in fatigue life to the insufficient diffusion of Fe, Cr, and Ni into the aluminum due to insufficient temperature increase [1]. Studies which tested other aluminum alloys and steels found similar results [2][3][4]. Others found an increase in hardness at the interface of the joint of AA5005 aluminum and St-52 steel, as well as AA1100 and A441 AISI steel, and attributed this quality to the formation of intermetallic compounds [5,6].…”
Section: Introductionmentioning
confidence: 66%
“…The authors of this study attributed the reduction in fatigue life to the insufficient diffusion of Fe, Cr, and Ni into the aluminum due to insufficient temperature increase [1]. Studies which tested other aluminum alloys and steels found similar results [2][3][4]. Others found an increase in hardness at the interface of the joint of AA5005 aluminum and St-52 steel, as well as AA1100 and A441 AISI steel, and attributed this quality to the formation of intermetallic compounds [5,6].…”
Section: Introductionmentioning
confidence: 66%
“…pin length. The pin thrusting distance [12] when compared to the butt line was 0.1 mm (0.0 mm thrusting distance was a location that the pin side touched the butt line as shown in Fig. 1b.…”
Section: Experimenal Peocedurementioning
confidence: 96%
“…However, it should be noted that the obtainment of good quality welding joints between aluminum and steel represents a considerable challenge because of their significant relative differences in their mechanical properties, physical properties, and melting temperatures. Specifically, iron–aluminum intermetallic compound (IMC) layers easily form hardened and brittle interface surface areas between the weld and the stainless steel side, which greatly reduces the strength of welded joint [ 9 , 10 , 11 ]. Therefore, in order to ameliorate this circumstance, many different welding methods have been utilized for the welding of aluminum alloys and stainless steel, including friction stir welding [ 4 , 12 ], metal inert gas welding [ 13 , 14 , 15 , 16 , 17 ], laser welding [ 5 , 18 , 19 , 20 , 21 ], resistance sport welding [ 22 ], and ultrasonic welding [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%